2016
DOI: 10.1016/j.ajem.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Who is prescribing controlled medications to patients who die of prescription drug abuse?

Abstract: Background: Prescription drug-related fatalities remain a significant issue in the United States, yet there is a relative lack of knowledge on the specialty-specific prescription patterns for drug-related deaths. Methods: We designed a study that investigated medical examiner reports of prescription drug-related deaths that occurred in San Diego County during 2013. A Prescription Drug Monitoring Program search was performed on each of these cases to ascertain which physician specialties had prescribed controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…One study examined the PDMP of more than 200 patients in San Diego whose deaths involved prescription drugs and found that less than a third qualified as “doctor shoppers.” However, almost three‐quarters had PDMP data in the year before their deaths, with frequent listings of hydrocodone, oxycodone, alprazolam, and clonazepam. Although it is possible that more consistent use of PDMPs could have prevented at least some of these overdoses, an appreciable subset of patients were procuring prescription agents from sources not covered by the California PDMP . Similarly, only a quarter of individuals arrested for trafficking Schedule II–IV drugs were found to have been prescribed those agents in the Maine PDMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study examined the PDMP of more than 200 patients in San Diego whose deaths involved prescription drugs and found that less than a third qualified as “doctor shoppers.” However, almost three‐quarters had PDMP data in the year before their deaths, with frequent listings of hydrocodone, oxycodone, alprazolam, and clonazepam. Although it is possible that more consistent use of PDMPs could have prevented at least some of these overdoses, an appreciable subset of patients were procuring prescription agents from sources not covered by the California PDMP . Similarly, only a quarter of individuals arrested for trafficking Schedule II–IV drugs were found to have been prescribed those agents in the Maine PDMP.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that more consistent use of PDMPs could have prevented at least some of these overdoses, an appreciable subset of patients were procuring prescription agents from sources not covered by the California PDMP. 12 Similarly, only a quarter of individuals arrested for trafficking Schedule II-IV drugs were found to have been prescribed those agents in the Maine PDMP. Further, more than half were receiving controlled prescription drugs from only one physician and one pharmacy, whereas only 14% and 7% used three or more prescribers and pharmacies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors have contributed to this opioid overdose epidemic, including availability of prescription and illicit opioids, unsafe prescribing of opioids, doctor shopping for opioids, and opiate diversion (Lev et al, 2016; Paulozzi, 2012). Opioid addiction is a chronic disease that often requires MAT for an adequate duration to facilitate recovery (Kampman and Jarvis, 2015; Volkow and McLellan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies demonstrate that patients discharged from surgical units leave significant quantities of their opioid analgesia unused and stored in the home . There is evidence that ED opioid analgesic prescribing leads to recurrent opioid use in the community and is a source of the prescription opioids implicated in many unintentional overdose deaths …”
Section: Introductionmentioning
confidence: 99%